The Relationship between Health Education and Mothers’ Knowledge, Attitudes, and Practices in Early Detection of Toddler Growth and Development - O'Connor, Winthrop; Kay, Kang (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This study aims to examine the effect of structured health education on mothers’ knowledge, attitudes, and practices in early detection of toddler growth and development at a community health center in Bangkalan, Indonesia. The study focuses on understanding how educational interventions influence maternal behavior in routine Posyandu services. Methodology: A pre-experimental one-group pretest–posttest design was employed. Data were collected using structured questionnaires and observation checklists. Health education was delivered through lectures, demonstrations, and discussions using flipcharts and leaflets. Participants were mothers with toddlers aged 12–36 months. Data were analyzed with descriptive statistics and the Wilcoxon signed-rank test. Main Findings: Health education significantly improved mothers’ knowledge, attitudes, and practices in early detection of toddler growth and development. Post-intervention scores increased for knowledge (45.2 → 68.7), attitudes (38.6 → 52.4), and practices (41.3 → 59.8), indicating effective translation of understanding and readiness into observable behavior during growth monitoring and developmental screening activities. Novelty/Originality of this study: This study integrates structured, hands-on health education with practical demonstrations at Posyandu, linking maternal knowledge and attitudes directly to behavior. Unlike previous research focusing on single KAP components, this approach evaluates all dimensions simultaneously in a real-world setting, offering new insights for designing effective, behavior-oriented maternal education programs in early childhood development monitoring.